Control of oestrous cycle in small ruminants - SAMARTZI (Φ. ΣΑΜΑΡΤΖΗ), F.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ), G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Control of oestrous cycle is an important management tool in sheep and goat farms. Over the years, various methods have been developed and many applications have been documented in the international literature. In this review paper, the theoretical background and practical aspects of oestrous cycle control in small ruminants are reviewed; furthermore, problems related to oestrous cycle control are discussed. The article is divided in the following sections: (i) Methods for the control of the oestrous cycle (selection of method, male effect, pharmaceutical methods), (ii) Methods for increasing ovulation rate (nutrition, genetics, hormonal treatment, immunization techniques), (iii) Induction of early puberty, (iv) Fertilization of animals (mating or artificial insemination), (v) Problems during application of oestrous control methods (side effects of treatments, application errors).